РЕЗУЛЬТАТЫ АРХЕОЛОГИЧЕСКИХ ИССЛЕДОВАНИЙ БОХАЙСКИХ МОГИЛЬНИКОВ В КНР - Юймэн, Хэ (Гуманитарные исследования в Восточной Сибири и на Дальнем Востоке, 2024)
The article summarizes the results of study of burial grounds and burials of Bohai state (698–926) located on the territory of China. Currently, more than twenty burial grounds and individual burials are known here, and in total about a thousand burials have been excavated. Most of Bohai burials are located in the valleys of four large rivers – the Second Songhua River, Mudanjiang River, Tumen River and Suifen River. Basing on the results of the work of Chinese researchers and structuring data on Bohai burials in accordance with the areas of their location, the author characterizes their local features and traces the process of their development in different eras.